The IMF's financial surveillance in Europe - experiences with FSAPs and their links with Article IV consultations - Marco Committeri; Juergen Arndt; Daniele Ciani; Maximilian Fandl; Maria Alessandra Freni; Serena Garelli; Marco Giornetti; Frank Heid; Caroline Janssens; Mary Keeney; Patrick Kosterink; Alexander Landbeck; et al. (European Central Bank (ECB), 2020)
Cross-border financial integration has increased the need to make suitable multilateral arrangements for global financial cooperation and oversight - these include more intense and more effective financial sector surveillance by the International Monetary Fund (IMF). The financial sector has a crucial role to play in addressing today's global health emergency, and it is important that it remains sufficiently resilient to facilitate the prompt return to more orderly economic conditions worldwide.
Keywords: 330